ELEKTRON O‘QUV METODIK TA’MINOTLARNI YARATISHDA SU’NIY INTELLEKT IMKONIYATLARIDAN FOYDALANISH - Kenesbayev, A. (SCIENCE and SOCIETY, 2025)
This paper is analyzed the possibilities and methods of use of artificial intelligence in the creation of e-learning methodologies. At the same time, information was provided on the role of these technologies in education, their advantages and future development directions